2010
DOI: 10.1128/aac.00220-10
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Travel Is a Major Risk Factor for Colonization with Escherichia coli Producing CTX-M-Type Extended-Spectrum β-Lactamases: a Prospective Study with Swedish Volunteers

Abstract: Foreign travel has been suggested to be a risk factor for the acquisition of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae. To our knowledge, this has not previously been demonstrated in a prospective study. Healthy volunteers traveling outside Northern Europe were enrolled. Rectal swabs and data on potential travel-associated risk factors were collected before and after traveling. A total of 105 volunteers were enrolled. Four of them did not complete the study, and one participant carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
194
5
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(230 citation statements)
references
References 32 publications
24
194
5
7
Order By: Relevance
“…Multiple logistic regression analysis showed that travel in the previous 12 months to Africa, Asia or Latin America is a risk factor for carriage of ESBL/pAmpC-E, which is in agreement with findings of others [7,28,29]. The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7].…”
Section: Discussionsupporting
confidence: 87%
“…Multiple logistic regression analysis showed that travel in the previous 12 months to Africa, Asia or Latin America is a risk factor for carriage of ESBL/pAmpC-E, which is in agreement with findings of others [7,28,29]. The findings of Reuland et al showing that the use of PPIs is a risk factor were confirmed [7].…”
Section: Discussionsupporting
confidence: 87%
“…Tangden et al associated gastroenteritis during travel with the risk for ESBL-E acquisition among travelers from Sweden ( 3 ). That association was not found in this study, which may reflect less fecal–oral contamination while traveling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Australia ( 13 ), Sweden ( 14 , 15 ), and the Netherlands ( 16 ) have shown that international travel is a major risk factor for colonization with ESBL-producing Enterobacteriaceae . Likely, these resistant strains are acquired from the environment during travel, e.g., through food consumption ( 17 ).…”
mentioning
confidence: 99%